Optimizing coral reef recovery with context-specific management actions at prioritized reefs. (1st October 2021) - Gouezo, Marine; Fabricius, Katharina; Harrison, Peter; Golbuu, Yimnang; Doropoulos, Christopher
Abstract: Assisting the natural recovery of coral reefs through local management actions is needed in response to increasing ecosystem disturbances in the Anthropocene. There is growing evidence that commonly used resilience-based passive management approaches may not be sufficient to maintain coral reef key functions. We synthesize and discuss advances in coral reef recovery research, and its application to coral reef conservation and restoration practices. We then present a framework to guide the decision-making of reef managers, scientists and other stakeholders, to best support reef recovery after a disturbance. The overall aim of this management framework is to catalyse reef recovery, to minimize recovery times, and to limit the need for ongoing management interventions into the future. Our framework includes two main stages: first, a prioritization method for assessment following a large-scale disturbance, which is based on a reef's social-ecological values, and on a classification of the likelihood of recovery or succession resulting in degraded, novel, hybrid or historical states. Second, a flow chart to assist with determining management actions for highly valued reefs. Potential actions are chosen based on the ecological attributes of the disturbed reef, defined during ecological assessments. Depending on the context, management actions may include (1) substrata rehabilitation actions to facilitate natural coral recruitment, (2) repopulating actions using active restoration techniques, (3) resilience-based management actions and (4) monitoring coral recruitment and growth to assess the effectiveness of management interventions. We illustrate the proposed decision framework with a case study of typhoon-damaged eastern outer reefs in Palau, Micronesia. The decisions made following this framework lead to the conclusion that some reefs may not return to their historical state for many decades. However, if motivation and funds are available, new management approaches can be explored to assist coral reefs at valued locations to return to a functional state providing key ecosystem services. Graphical abstract: Image 1 Highlights: We present a two-stage decision framework for managers to assist reef recovery. Stage one scores reefs by their social-ecological values and likelihood for recovery. Stage two is a flow chart to prioritize specific management actions. Ecological monitoring needs to underpin management actions taken at prioritized reefs. A case study from Palau is presented to test this decision framework.